Reinventing Another Unaipon: Indigenous Science Leaders for the Future - Trimmer, Karen; Gower, Graeme; Lock, Graeme (The Australian Journal of Indigenous Education, 2017)
The education of Indigenous and Torres Strait Islander students in Australian universities has received considerable attention in both the literature and government policy in the 21st century. The participation and graduation rates for Indigenous and Torres Strait Islander students in higher education Science, Technology, Engineering and Mathematics (STEM) programs have remained low and are becoming a particular focus in universities across Australia. This paper reflects on the life and contribution of David Unaipon, the enrolment data from a small sample of universities across Australia and the literature to discuss potential strategies for improving the access to, participation in and graduation from higher education STEM courses.